Issues cliniques des patients autochtones victimes d'un empoisonnement dans le continuum de soins : une étude de cohorte rétrospective multicentrique - Diendere, Ella (Université Laval, 2019)
Background Indigenous population have a high incidence of poisoning cases across Canada, which is associated with high morbidity and mortality. A suboptimal provision of health care was suggested to explain suchburden. Unfortunately, very little information is available to describe the specific presentations of poisoning cases in Indigenous populations. There fore, our study aims to assess whether differences exist in the continuum of care of poisoned patients living in rural regions in Quebec, Canada, according to their ethnic origin. Methods We conducted a multicenter retrospective cohort study using data from the Centre antipoison du Québec (CAPQ) between 2016 and 2017. Indigenous poisoned patients were compared to non Indigenous patients living in rural areas. Our main outcome was the duration of involvement by the CAPQ in case management, reflecting the time required to complete toxicological management. Generalized linear regression was used to evaluate differences in the duration of poison center involvement between the two populations. A sex-specific analysis was also conducted. Our secondary outcome was the symptom severity at the conclusion of management. Results Among 362 identified poisoned patients (184 Indigenous and 178 non-Indigenous), we observed no differences in the duration of case management between groups (GMR adjusted = 1.09; [95% CI 0.87;1.38]). Moreover, the sex-specific analysis showed that the association was not significant in either male or female groups. High proportion of patients, in both Indigenous and non-Indigenous groups,showing mild to moderate symptoms at follow-up (78%). One death was registered in each group. The CAPQ received very few calls from the non-conventioned First Nations during the study period. Interpretation We did not observe any difference on the duration in case management of cases between patients living in rural areas. Perceptions of suboptimal care provided to rural Indigenous population are likelyto be related to geographical remoteness rather than ...